Recent Booh By Academy Members: Introduction to Behavioral Science for BusinessJohn Wiley and Sons, Inc. (654 pages, $10.95) - Kolasa, Blair J. (Academy of Management Journal, 1969)
The article reviews the book ?Introduction to Behavioral Science for Business,? by Blair J. Kolasa.